Pembelajaran Problem Based Learning Berbantuan Wordwall Ditinjau dari Motivasi Belajar Siswa - Sela Nur Amelia Sandi; Chika Rahayu; Helni Indrayati (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
This study aims to see the learning motivation of students using a problem-based learning model assisted by wordwalls on the subject of the Cartesian coordinate system. The type of research is an experiment with the research design used, namely pre-test and post-test control group design. The population in this study was all grade VIII students of SMP MTs Negeri 1 Pagaralam. The samples used in this study are class VIII.3 (experimental class) and class VIII.5 (control class). Data collection uses documentation, tests and questionnaire methods. Then the data was processed using a statistical test of the t-test. Based on the results of the study using a problem-based learning model assisted by a wordwall, the average percentage of motivation indicators in the experimental class is 85.22%, which can be said to be very strong, and the average percentage of motivation indicators in the control class, which is 76.65%, can be said to be strong. So it can be seen that the motivation score for learning mathematics using the wordwall-assisted problem-based learning model has a high level of motivation after using the wordwall-assisted problem-based learning learning model. Keywords: PBL, Learning Motivation, Wordwall, Coordinate Cartesius